'Reining In' Special Education: Constructions of "Special Education" in New York Times Editorials, 1975-2004 - Rice, Nancy (Disability Studies Quarterly, 2006)
The media claim to speak with authority on educational issues and thus play a major role in the construction of public messages about special education. Discursive constructions of "special education" portray the landscape of possibilities within which much of the public comes to understand what special education is, influencing their understanding and judgment of it. The purpose of this paper is to analyze public constructions of "special education" using editorials published in The New York Times from 1975-2004. Using critical discourse analysis, this paper reveals themes developed over time as well as the ways language is used to construct a particular view of "special education." Alternative discourses are suggested to counter the hegemonic presentations by the Times editors.